Укрощение любовью: роман / Холли Уорнер - Уорнер Холли (Панорама романов о любви, 1995)
Экземпляры: ф.18 (20181023) / Инвентарный номер: 041567 / Цена: 3800.00 / Авт.знак: У 64 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)